1987
DOI: 10.1111/j.1525-1470.1987.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Impetigo: A Reassessment of Etiology and Therapy

Abstract: Traditional concepts regarding the bacteriology and therapy of nonbullous impetigo have been reexamined. Although in the United States the disease is considered primarily of streptococcal origin and amenable to penicillin therapy, we found that Staphylococcus aureus was the most common isolate in 71 patients studied. Only two patients yielded pure cultures of group A beta-hemolytic streptococci. All but two isolates of S. aureus were resistant to penicillin; one of these two isolates was also resistant to eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Because S. aureus currently accounts for most cases of bullous impetigo, as well as for a substantial portion of nonbullous infections [13,19,20], penicillinaseresistant penicillins or first-generation cephalosporins are preferred (A-I), although impetigo caused by MRSA is increasing in frequency [13] (table 2). Erythromycin has been a mainstay of pyoderma therapy, but its utility may be lessened in areas where erythromycin-resistant strains of S. aureus, or more recently, S. pyogenes, are prevalent.…”
Section: Impetigomentioning
confidence: 99%
“…Because S. aureus currently accounts for most cases of bullous impetigo, as well as for a substantial portion of nonbullous infections [13,19,20], penicillinaseresistant penicillins or first-generation cephalosporins are preferred (A-I), although impetigo caused by MRSA is increasing in frequency [13] (table 2). Erythromycin has been a mainstay of pyoderma therapy, but its utility may be lessened in areas where erythromycin-resistant strains of S. aureus, or more recently, S. pyogenes, are prevalent.…”
Section: Impetigomentioning
confidence: 99%
“…Of (9,12,13,18,21,22). More recently, many studies from various parts of the world showed that the predominant organism in the disease was S. aureus, isolated alone or with streptococci from 65 to 98% of the patients (1,5,7,8,14,16,19,20). Furthermore, failure rates with penicillin and amoxicillin were unacceptably high, ranging from 20 to 47% (1,7,8) and suggesting that S. aureus was not just an innocent bystander but rather played an important role in the disease as either a primary or a secondary pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…Erythromycin is considered an appropriate drug for impetigo, since it is a nontoxic, relatively inexpensive drug active against both staphylococci and streptococci (1,6,10,17). In fact, it was even claimed that erythromycin may be the preferred drug on the basis of cost effectiveness (2,8).…”
Section: Resultsmentioning
confidence: 99%
“…In studies conducted over the past three decades, there has been a resurgence of S. aureus as the main agent of crusted impetigo. 16-24 S. aureus , alone or in combination with group A beta hemolytic streptococci, is responsible for about 80% of the cases, being the most frequently recovered isolated agent. Although we have not found any Brazilian studies conducted in recent decades regarding the epidemiology of impetigo, these data are corroborated in studies conducted in different countries, such as United States, Israel, Thailand, Guyana, India, Chile, and Japan.…”
Section: Non-bullous Impetigo (Crusted)mentioning
confidence: 99%